Fault-tolerance techniques for spacecraft control computers - Yang, Mengfei; Hua, Gengxin, 1965-; Feng, Yanjun, 1969-; Gong, Jian, 1975- (John Wiley & Sons, Inc., 2017)
Comprehensive coverage of all aspects of space application oriented fault tolerance techniques - Experienced expert author working on fault tolerance for Chinese space program for almost three decades- Initiatively provides a systematic texts for the cutting-edge fault tolerance techniques in spacecraft control computer, with emphasis on practical engineering knowledge- Presents fundamental and advanced theories and technologies in a logical and easy-to-understand manner- Beneficial to readers inside and outside the area of space applications.